What happened to entrepreneurial economies after the financial crisis? An empirical study of OECD countries - Jean Bonnet; Rafik Abdesselam; Patricia Renou-Maissant; Mathilde Aubry (European Regional Science Association (ERSA), 2015)
The aim of this paper is to analyze entrepreneurial activity in OECD countries over the period 1999-2012 in order to make a distinction between economies that are more or less entrepreneurial. A combined use of multidimensional and evolutive data analysis methods is used with variables pertaining to entrepreneurial activity and growth. It allows us to distinguish several types of development. Furthermore, three main periods are found, before, during and after the crisis. The pre-crisis period, from 1999 to 2008, was a period of growth favorable to entrepreneurship while the sub-period 2010-2012 is less favorable. The effects of the financial crisis are noticeable after a delay in 2009. We show that in 2009, the agricultural economies have best withstood the financial crisis. Secondly, during the period 2010-2012 after the crisis, economies widely dependent on the financial sector were most impacted by the financial crisis. Because of the financial crisis, the entrepreneurial dynamics vary greatly across countries over the period 1999-2012, however we were able to establish common trajectories for a number of them
Keywords: L26; C38; O1; 330; Entrepreneurship; Data analysis methods; Entrepreneurial/Administrated economies